2010
DOI: 10.3176/eng.2010.2.04
|View full text |Cite
|
Sign up to set email alerts
|

On non-destructive residual stress measurement in glass panels

Abstract: A portable scattered light polariscope SCALP has been developed, which permits measurement of the residual stress profile through the thickness of glass panels. At a glass factory strength assessment of glass panels of different thermal treatment was carried out using both residual stress measurement with SCALP and the traditional four-point bending tests. Linear correlation between the residual surface stress and the bending strength was observed. At another glass factory residual stress in glass panels was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…For instance, using SCALP-05, the surface compression in float, heat-treated and tempered glass specimens were determined to be ;7, 120 and 160 MPa, respectively. 18 The potential of SCALP-05 to measure stresses along the thickness of glass was also exploited in the literature: for instance, stresses up to a depth of ;2.2 mm were determined in float, tempered and chemically toughen glass specimens. 20 The research presented in the literature suggests the potential of SCALP-05 to measure residual stresses present in float glass, and as it will be shown in the latter half of this article, the results of SCALP-05 were used to validate the predictions of the contour method/eigenstrain hybrid model proposed in this article.…”
Section: Experimental Investigations Of Residual Stress In Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, using SCALP-05, the surface compression in float, heat-treated and tempered glass specimens were determined to be ;7, 120 and 160 MPa, respectively. 18 The potential of SCALP-05 to measure stresses along the thickness of glass was also exploited in the literature: for instance, stresses up to a depth of ;2.2 mm were determined in float, tempered and chemically toughen glass specimens. 20 The research presented in the literature suggests the potential of SCALP-05 to measure residual stresses present in float glass, and as it will be shown in the latter half of this article, the results of SCALP-05 were used to validate the predictions of the contour method/eigenstrain hybrid model proposed in this article.…”
Section: Experimental Investigations Of Residual Stress In Glassmentioning
confidence: 99%
“…SCALP-05 was calibrated 18 using the experimental results of four-point bending experiments conducted in accordance with EN 1288-3 19 and the stresses measured using GASPs. For instance, using SCALP-05, the surface compression in float, heat-treated and tempered glass specimens were determined to be ;7, 120 and 160 MPa, respectively.…”
Section: Experimental Investigations Of Residual Stress In Glassmentioning
confidence: 99%
“…Figure 6d also shows an optical micrograph of an actual secondary crack for the same conditions. The stress in the tested plate was measured prior to fracture by standard optical methods, as described by Aben et al (2010). It was found that the fracture surface predicted by the model accurately depicts the location and the shape of the mirror-mist boundary region.…”
Section: Evaluation Of the Crack Evolution Modelmentioning
confidence: 99%
“…These significant compressive stresses at the surface act as crack-closing forces. This increases the bending strength of tempered glass plates by an amount approximately equal in magnitude to the residual stress at the surface (Aben et al 2010;Conway and Mecholsky 1989). An additional distinctive feature of tempered glass is the high degree of fragmentation at fracture.…”
Section: Introductionmentioning
confidence: 95%
“…The intensity of the scattered light depends on the birefringence caused by the stresses. This opens up the possibility to measure the distribution of the residual stresses through the thickness of glass objects [6][7][8]. Figure 3a shows the scattered light measurement scheme.…”
Section: The Scattered Light Methodsmentioning
confidence: 99%